KAJIAN PENGELOLAAN EKOWISATA BERBASIS EKONOMI DAN SOSIAL (Studi Kasus Semenanjung Nusaniwe Kota Ambon Provinsi Maluku) - Yensy L. Salamor; Semmy Limba; Debby V. Pattimahu (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2017)
The potential of the historical and cultural society at the state of Nusaniwe with potential for agro-tourism, nature tourism potential that Pintu Kota Beach, Felawatu beach, Bethesda Beach, natural scenery of Gunung Dua, Lapoci and waterfalls Laponot. The latter is a country with tourist potential Latuhalat Santai Beach, Namalatu Beach, Sumber Jaya Beach and Tanjung Batu Konde beach. While seasonal travel is labor time culture. As for the tourism potential of the cultural history of the community, Batu Bicara, and Clump Bamboo Baduri. The aim of the research is identifying potential tourist attraction in Peninsula Nusaniwe comprehensively, analyze the economic value attraction Nusaniwe Peninsula, analyze the relationship between socioeconomic peninsula Nusaniwe with ODTW and Ecotourism Management Formulate strategies based on economic value and social area. The method used is (1) travel cost method to calculate the economic value of the tourist area, (2) the method of Chi-square to see the relationship with the community characteristics ODTW (3) exponential comparison method (MPE) to formulate priorities Ecotourism development strategy. The results showed that the tourism potentials in the Peninsula Nusaniwe namely to State Amahusu the tourism potential of the coast is Batu Capeu, Batu Lubang, Waititei Beach, Pasir Putih Beach. Based on chi-square analysis shows that there is a relationship between family income through community participation towards ODTW. Priorities ODTW development strategy is the development of supporting infrastructure Optimization of travel (22,26%), ecotourism Develop sustainable policies (20,56), improve coordination between government and stakeholders managing ecotourism (18,30), creation of a conducive investment climate (14,95%), strengthening of human resource capacity in the utilization ODTW (13,40%), Improving access to information and the promotion of communications (10,53%).